2023
DOI: 10.1136/bmjopen-2022-067007
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported burden and overall impact of dry eye disease across eight European countries: a cross-sectional web-based survey

Abstract: ObjectiveDry eye disease (DED) is a multifactorial disease involving the tears and ocular surface. It impacts a patient’s quality of life (QoL) and ability to perform daily activities. This study assessed the burden of self-reported DED among adults in eight European countries.DesignOnline cross-sectional survey.SettingGeneral population in France, Italy, Germany, Greece, the Netherlands, Portugal, Spain and Sweden.ParticipantsAdults aged ≥18 years with (n=6084) and without (n=6161) self-reported DED were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Consistent with most previous studies, we found a higher prevalence among women and older age groups. 1 , 3 , 6 Reasons for the higher prevalence of DED in women include hormonal differences and changes during pregnancy and menopause, higher rates of autoimmune diseases, but also higher contact lens use and cosmetic use. 28 In addition, there is evidence that men might tend to under-report symptoms, which has been reported previously, also in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with most previous studies, we found a higher prevalence among women and older age groups. 1 , 3 , 6 Reasons for the higher prevalence of DED in women include hormonal differences and changes during pregnancy and menopause, higher rates of autoimmune diseases, but also higher contact lens use and cosmetic use. 28 In addition, there is evidence that men might tend to under-report symptoms, which has been reported previously, also in Germany.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Recently, 6084 adults were investigated across 8 European countries. 3 Participants with self-reported DED reported lower functional vision, a lower overall health status, and more work productivity impairment. Similarly, in a large Dutch population-based cohort (n = 78,165), self-reported DED was associated with substantial reductions in all domains of health-related quality of life (HRQoL) measured by the Short Form 36 (SF-36), also after correcting for common comorbidities such as chronic pain, rheumatologic, and mental disorders.…”
Section: Dry Eye Diseasementioning
confidence: 97%
“…This prevalence of DED increases with age, particularly in those over 40, and is more common among women than men [2] . DED has a significant impact on visual acuity, which affects the quality of life of affected patients [3][4] . Patients are classified as having aqueous deficiency due to lacrimal dysfunction or evaporative DED associated with meibomian gland dysfunction (MGD).…”
Section: Introductionmentioning
confidence: 99%
“…As the Chinese population ages and life expectancy rises, DED will remain one of the leading causes of ophthalmic illness ( Song et al, 2018 ; Cai et al, 2022 ). Patients typically experience various symptoms, such as photophobia, fatigue, itchiness, burning, and visual disturbance, and some may even experience severe visual problems and blindness in the later stages if treatment is delayed ( Boboridis et al, 2023 ). Meanwhile, those with DED must bear a substantial economic burden and develop psychological problems such as anxiety and depression during prolonged therapy, making DED an important public health problem ( Chan et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%